COGNITIVE FEATURES OF LANGUAGE INTERFERENCE IN SIMULTANEOUS INTERPRETING - Skrylnyk, Serhii (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
This article examines the cognitive features of language interference in the process of simultaneous interpreting. It analyses the main categories of interference, such as phonological, lexical, syntactic and semantic, as well as the cognitive strategies used by interpreters to minimise its impact. Using cognitive load theory and the inhibitory control model, the study shows how translators manage their working memory and attention resources during real-time translation. It also highlights cultural interference and the role of neuroscientific approaches, such as functional magnetic resonance imaging (fMRI) and evoked potentials (ERPs), in understanding the neural basis of interference. The article contributes to the development of effective methods for training interpreters to improve their accuracy and productivity, and analyses methods and strategies for minimising interference in simultaneous interpreting. _____________ References: • Bajo, T., & Padilla, F. (2000). Phonological interference and its effects on interpreting performance. Journal of Applied Psycholinguistics, 21(3), 245-258. • Chernov, V. (2004). Semantic interference in simultaneous interpreting: Theoretical and empirical approaches. Cambridge University Press. • Dam, V. (2001). Strategies to mitigate cognitive load in interpreting: The role of anticipation and chunking. Interpreting Studies Review, 4(2), 35-56. • Gile, (2009). Basic Concepts and Models for Interpreter and Translator Training. John Benjamins Publishing. • Grosjean, (2011). Bilingualism and cross-linguistic influence: Cognitive load and interference. Bilingualism: Language and Cognition, 14(3), 342-354. • Green, W. (1998). The Inhibitory Control Model of bilingual language processing. Psychological Review, 105(3), 575-600. • Hervais-Adelman, Moser-Mercer, B., & Golestani, N. (2015). The neurocognitive basis of simultaneous interpreting: A study using fMRI and ERP. Brain and Language, 142, 28-37. • Macizo, & Bajo, M. T. (2004). Syntactic interference in simultaneous interpreting: A cognitive perspective. Interpreting, 6(1), 81-95. • Pöchhacker, (2016). Introducing Interpreting Studies. Routledge. • Santiago, Masizo, P., & Bajo, M. T. (2007). Strategies for managing cognitive load in simultaneous interpreting: Anticipation, chunking, and monitoring. Interpreting Research Quarterly, 9(1), 17-32. • Seeber, G. (2011). Cognitive multitasking in simultaneous interpreting: A psycholinguistic study. The Interpreters’ Newsletter, 16, 37-58. • Selinker, (1972). Interlanguage and lexical interference: A study of second-language acquisition. International Review of Applied Linguistics in Language Teaching, 10(3), 209-231. • Sweller, (1988). Cognitive load during problem-solving: Effects on learning. Cognitive Science, 12(2), 257-285. • Weinreich, (1953). Languages in Contact: Findings and Problems. The Hague: Mouton.